7x-29-19x=3-12-2x

Simple and best practice solution for 7x-29-19x=3-12-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-29-19x=3-12-2x equation:


Simplifying
7x + -29 + -19x = 3 + -12 + -2x

Reorder the terms:
-29 + 7x + -19x = 3 + -12 + -2x

Combine like terms: 7x + -19x = -12x
-29 + -12x = 3 + -12 + -2x

Combine like terms: 3 + -12 = -9
-29 + -12x = -9 + -2x

Solving
-29 + -12x = -9 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-29 + -12x + 2x = -9 + -2x + 2x

Combine like terms: -12x + 2x = -10x
-29 + -10x = -9 + -2x + 2x

Combine like terms: -2x + 2x = 0
-29 + -10x = -9 + 0
-29 + -10x = -9

Add '29' to each side of the equation.
-29 + 29 + -10x = -9 + 29

Combine like terms: -29 + 29 = 0
0 + -10x = -9 + 29
-10x = -9 + 29

Combine like terms: -9 + 29 = 20
-10x = 20

Divide each side by '-10'.
x = -2

Simplifying
x = -2

See similar equations:

| X^2+12=16 | | 23x+6-25x=4-8 | | 6x=2(8x+25) | | 2-6p=-13+p+-5p | | 6x(3x+5)+14=5x-13 | | X+2=-3x+1 | | -19.95+1.10h=-2.35 | | 6x=2-(-16) | | 6x=-22(-16) | | -10+x+35=47+(-12) | | -5(x+1)-16=21+3 | | 1.2x+43=2.1-x | | -74+x=-25 | | 8(x-5)+7x=15x+15 | | -2x+4x-33=15 | | 120=(2x-10) | | 10.8-0.2h=9 | | -10u+21=-12u-9 | | 46y=5(9y-4) | | 5y+5+3y-y=26 | | 1.25-t=3+1.5t | | 2x+0.75=101 | | 7.46=2(3.14) | | (x+3)(x+3)=x^2+6x+9 | | -6+6z-4=-34 | | 21u-24=-9u-10 | | -30x=-240 | | 3X+8-2x=14 | | 5.6-0.32h=1.12 | | 12.5d+4=4.3d+35.16 | | -5x-5x=72-2 | | -6(-n)=8 |

Equations solver categories